Microbial biotransformation to obtain stilbene methylglucoside with GPR119 agonistic activity - Peng, Yu; Huan, Yi; Chen, Jing-Jing; Chen, Tian-Jiao; Lei, Lei; Yang, Jin-Ling; Shen, Zhu-Fang; Gong, Ting; Zhu, Ping (Frontiers in Microbiology, 2023)
Microbial transformation of piceatannol (PIC) and resveratrol (RSV) using Beauveria bassiana has produced three new methylglucosylated derivatives of PIC (1-3) and two known RSV methylglucosides (4 and 5). Structures of the new metabolites were characterized as 3-O-(4''-O-methyl-β-D-glucopyranosyl)-piceatannol (3-O-MG PIC, 1), 4'-O-(4''-O-methyl-β-D-glucopyranosyl)-piceatannol (4'-O-MG PIC, 2), and 3'-O-(4''-O-methyl-β-D-glucopyranosyl)-piceatannol (3'-O-MG PIC, 3) by NMR spectroscopy and high resolution mass spectroscopic data. Among them, 1 not only showed moderate GPR119 agonistic activity with 65.9 % but also promoted insulin secretion level significantly (12.94 ng/mg protein/hour) at 1 μM. After the optimization of fermentation conditions, the yield of 1 reached 45.53%, which was increased by 4.2-fold compared with the control. Our work presents that 3-O-MG PIC (1) is an effective and safer ligand targeting GPR119 using biotransformation method, which lays a foundation for the anti-diabetic drug design in the future.